2016
DOI: 10.1097/mib.0000000000000926
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Anti-IFI16 and Anti-GP2 Antibodies in Inflammatory Bowel Disease and Their Variation with Infliximab Therapy

Abstract: Our results highlight the importance of IFI16 in IBD pathogenesis showing that its de novo overexpression in the gut epithelial cells leads to a breakdown in immune tolerance and the subsequent development of specific autoantibodies. Anti-IFI16 IgG antibodies hold the potential to serve as a biomarker of response to IFX therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
2
23
0
1
Order By: Relevance
“…The transcriptional data correlated well with immunoblotting studies exhibiting increased protein expression of AIM2 and IFI16 in the colonic mucosa of active patients (Vanhove et al, 2015). These findings were independently verified by a study which confirmed elevated expression by immunohistochemistry of IFI16 in intestinal samples from both ulcerative colitis and Crohn's disease patients (Caneparo et al, 2016). Moreover, the latter study revealed elevated IFI16 expression limited to the intestinal epithelial cells of IBD patients.…”
Section: Ifi16 Assembles An Inflammasome In the Nucleussupporting
confidence: 76%
See 1 more Smart Citation
“…The transcriptional data correlated well with immunoblotting studies exhibiting increased protein expression of AIM2 and IFI16 in the colonic mucosa of active patients (Vanhove et al, 2015). These findings were independently verified by a study which confirmed elevated expression by immunohistochemistry of IFI16 in intestinal samples from both ulcerative colitis and Crohn's disease patients (Caneparo et al, 2016). Moreover, the latter study revealed elevated IFI16 expression limited to the intestinal epithelial cells of IBD patients.…”
Section: Ifi16 Assembles An Inflammasome In the Nucleussupporting
confidence: 76%
“…Although data was not included, IFI16 staining was conspicuously absent in intestinal epithelial cells from other non-IBD inflammatory conditions (Caneparo et al, 2016).…”
Section: Ifi16 Assembles An Inflammasome In the Nucleusmentioning
confidence: 99%
“…In the same setting, the dermal inflammatory infiltrate has been found positive for IFI16 staining indicating that IFI16 is aberrantly expressed also in lymphocytes, fibroblasts, and endothelial cells. Similarly, we and others have also recently demonstrated that IFI16 is aberrantly expressed in the intestinal mucosa of patients affected by IBD, where dysregulation of host–microbial interactions has been shown to play a major pathogenic role ( 153 , 154 ). In addition, we and others have evaluated the etiopathogenic role of PYHIN proteins in the development of SLE in human pathology as well as in mouse models (Table 1 ).…”
Section: Novel Functions For Ifi16 To Trigger Inflammationsupporting
confidence: 63%
“…Anti-OmpC positivity was associated with a lack of response to anti-TNF therapy at 1 year and increased likelihood of therapy discontinuation in UC patients ( 73 ). Low baseline levels of IgG antibodies against the pattern recognition receptors IFI16 were associated with clinical response to infliximab induction treatment in UC ( 74 ). Several studies tested the capacity of the serological marker perinuclear anti-neutrophil cytoplasmic antibodies (pANCA) to predict response to anti-TNF agents.…”
Section: Patient and Disease Related Predictors To Anti-tnf Therapymentioning
confidence: 99%